The role of organ-deposited IgG in the pathogenesis of multi-organ and tissue damage in systemic lupus erythematosus - Qiu, Wenlin; Yu, Tong; Deng, Guo-Min (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is a severe chronic autoimmune disease characterized by multi-organ and tissue damage and high levels of autoantibodies in serum. We have recently investigated the role of autoantibodies in the pathogenesis of skin injury, joint, spleen, and liver damage in SLE through animal models to understand the role of organ-deposited SLE IgG in the pathogenesis of organ and tissue damage in SLE. We found that lupus serum triggered inflammation in tissue and organ, but not healthy serum, and the severity of inflammation was related to the dose of lupus serum. Immunohistochemistry displayed that a large number of IgG get deposited at the site of organ and tissue damage in lupus mice, and IgG is the major contributor to the development of tissue inflammation triggered by lupus serum. Monocytes/macrophages but not lymphocytes and neutrophils are required to develop tissue inflammation induced by lupus serum IgG; TNF/TNFR1 and IL-1 play essential roles in the development of tissue inflammation triggered by lupus IgG. TNFR1 inhibitors can suppress skin injury in lupus mice. Spleen tyrosine kinase (Syk) inhibitor, which can block signaling transduction of IgG/FcγRs, can prevent and treat skin injury and kidney damage in lupus mice. We also observed that lupus IgG might protect against bone erosion. Based on these results, we conclude that lupus IgG plays a crucial role in developing organ and tissue damage in SLE and in protecting bone erosion in SLE arthritis and IgG/FcγRs signaling pathway is an important therapeutic target in SLE.